Self-reported strategies for maintaining adherence to antiretroviral therapy in men aged 21 - 49 - Voget, Jacqueline Olivia (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.